Picnic Parties, Photography and Primates: Heginbotham's Tea Gardens, Kilbirnie - Marshall, Natalie (Architectural History Aotearoa, 2025)
Heginbotham's Tea Gardens was the last of Wellington's five pleasure gardens to open and it was at its peak in the early 1900s. Opened in Kilbirnie in 1891, the gardens advertised its summerhouse, ocean views, and "endless amusement in the antics of … monkeys in a cage," as well refreshments in a curated outdoor recreational space. These were fairly typical attractions for New Zealand's pleasure gardens, but Heginbotham set his venue apart by having a photographic studio onsite. From 1842, when the country's first tea garden opened, pleasure gardens had a popular form of entertainment, and made "a major contribution to the social life of Wellington" in the nineteenth century. These were public places that women could visit unaccompanied by men and socialise outside the home. By the early twentieth century, however, interest was waning in this form of entertainment, and the expansion of Wellington's suburbs was encouraging subdivision. Alongside sweeping urban and social change was a growing appreciation for New Zealand's natural environment. By the mid-1920s, Wellington's pleasure gardens had largely disappeared. This paper explores the role of these gardens and considers their legacy.